Influence of artefact correction and recording device type on the practical application of a non-linear heart rate variability biomarker for aerobic threshold determination; Sensors; Vol. 21, iss. 3 - Rogers B. Bruce; Giles D. A. David; Draper N. Nick; Mourot L. Laurent; Gronwald T. Thomas (2021, 2021)
Title screen